Analisis Kualitas Layanan Virtual Router Redundancy Protocol Menggunakan Mikrotik pada Jaringan VLAN - Muhammad Yusuf Choirullah; Muhammad Anif; Agus Rochadi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
In maintaining stability of communication in a complex network, such as Virtual Local Area Network (VLAN), a protocol that can keep the communication working is required. Virtual Router Redundancy Protocol (VRRP) is a protocol used to maintain communication by implementing the redundancy system on the router. When the main interface has problems, VRRP will automatically move the communications to backup interface. The result shows that long downtime can be avoided, hence, the communication process is maintained. This paper discusses VRRP analysis by comparing network topology using VLAN and LAN network. The networks are used to transfer data from cloud storage. The result shows that VRRP is able to maintain communication process when the main communication link is broken. The QoS downtime in VRRP VLAN and LAN with link failure are between 3.052 seconds to 6.475 seconds. The average downtime with bandwidth of 0 Mbps, 20 Mbps, 50 Mbps, 100 Mbps, and using the internet are, respectively, 3.6 seconds, 3.7 seconds, 3.9 seconds, 4.4 seconds, and 4.8 seconds. Interruption of communication can be solved in a short time. Compared to VRRP with LAN, VRRP with VLAN has more excellent quality of services, indicated by low value of downtime, more optimal throughput values, and minimal delay.